Notulae ad floram Sloveniae - Jogan, Jernej (Hladnikia (Ljubljana), 1998)
Razširjenost po prvi najdbi v Sloveniji
Keywords: fitogeografija; flora; florae; phytogeography; Slovenia; Slovenija; vegetacija; vegetation